Peer-Reviewer Round Table Response to Ted Riecken’s Scholarly Podcast, “Mapping the Fit Between Research and Multimedia: A podcast exploration of the place of multimedia within / as scholarship” - Leggo, Carl; Paré, Anthony; Riecken, Ted (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
Beginning with the question of blind peer review in the shifting landscape of multimedia publishing, and concluding with reflections on knowledge-creation in today’s academic culture, Riecken, Leggo, and Paré respond to Riecken’s podcast-article and reflect on the challenges of multimedia and other non-traditional forms of scholarship for the academy and for scholarly communication. Leggo and Paré were the peer reviewers for Riecken’s article, which is part of this same issue and can be listened to here: http://mje.mcgill.ca/article/view/9061. Since they hail from the same vicinity, they convened an author-peer reviewer round-table discussion on the issues raised in writing and reviewing a multimedia article. We are pleased to share their conversation.